Prehospital Determinants of Death-on-Arrival Among Emergency Department Patients at Waluyo Jati Kraksaan Hospital, Indonesia - Kusyairi, Achmad; Nusantara, Ana Fitria; Yuniarsih, Bidriah (Chakra Brahmanda Lentera Institute, 2026)
Background: Death on Arrival (DOA) refers to patients who arrive at the hospital with no signs of life and are declared dead without resuscitation because death has already occurred. Many DOA cases are potentially preventable through timely and appropriate prehospital emergency care. This study aimed to identify determinants associated with DOA among patients presenting to the Emergency Department of Waluyo Jati General Hospital, Kraksaan, Probolinggo, Indonesia. Methods: A quantitative analytical study with a cross-sectional design was conducted using secondary data from medical records of 70 DOA patients admitted between January and December 2024. Total sampling was employed to include all eligible cases. Independent variables comprised prehospital care, first responder capability, and type of initial case. Multivariable logistic regression was performed to determine factors independently associated with DOA, with results reported as odds ratios (ORs) and 95% confidence intervals (CIs). Results: Inappropriate prehospital care was identified in 95.7% of cases, while 92.8% of patients did not receive assistance from a competent first responder. Multivariable logistic regression demonstrated that inappropriate prehospital management was the only independent predictor significantly associated with DOA (OR = 3.50, 95% CI = 1.29–9.48, p = 0.014). First responder capability and type of initial case were not independently associated with DOA after adjustment. Conclusion: Inadequate prehospital management is the principal determinant associated with DOA. Strengthening prehospital emergency medical services, improving response time and treatment quality, and enhancing first responder competency are critical strategies to reduce preventable prehospital mortality and improve emergency care outcomes